2015
DOI: 10.1108/maj-02-2014-0997
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility disclosures and earnings quality

Abstract: Purpose -This paper aims to explore the relationship between corporate social responsibility (CSR) disclosures and earnings quality proxied by earnings accruals. Specifically, we examine whether CSR disclosures are context-specific, that is, whether companies dominated by powerful stakeholders are obliged to behave in a responsible manner to constrain earnings management, thereby reporting higher-quality earnings to investors. Design/methodology/approach -This paper explores the relationship between CSR disclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
111
3
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 158 publications
(136 citation statements)
references
References 66 publications
13
111
3
9
Order By: Relevance
“…findings do not lend support to our alternate hypothesis H 1 . These findings are consistent with the results of Muttakin et al (2015) and Prior et al (2008), who argue that the managers are using CSR activity and report as opportunistic incentive to cover up company misconduct. All the variables are defined in Table 2.…”
Section: Growthsupporting
confidence: 90%
See 4 more Smart Citations
“…findings do not lend support to our alternate hypothesis H 1 . These findings are consistent with the results of Muttakin et al (2015) and Prior et al (2008), who argue that the managers are using CSR activity and report as opportunistic incentive to cover up company misconduct. All the variables are defined in Table 2.…”
Section: Growthsupporting
confidence: 90%
“…Along the same line Gil et al, 2016, note that a greater engagement in CSR activity signals EQ and managers are trying to satisfy all the firms' stakeholders, using a data set from Spanish companies. Another viewpoint of research, the associate negative link between CSR and EQ (Muttakin et al, 2015;Prior et al, 2008), concluded that managers are using CSR activity and report as opportunistic incentive to cover up company misconduct. Supporting this viewpoint Martinez-Ferrero et al 2015, argue that managers might engage in CSR activity and disclosure to compensate for poor EQ.…”
Section: Content Analysis Csrd Ethical Hypothesis Transparency Earninmentioning
confidence: 99%
See 3 more Smart Citations